Penggunaan Digital Learning Material dalam Pembelajaran di Sekolah Dasar untuk Menghadapi Revolusi Industri 4.0 - Hatma Heris Mahendra; Fajar Nugraha; Riga Zahra Nurani; Missi Hikmatyar (Journal of Empowerment Community, 2020)
The industrial revolution emphasizes the definition of the speed element of information availability, which is an industrial environment in which all entities are always connected and able to share information with one another. The industrial revolution 4.0 has a big influence on the course of learning in the classroom in the future. One of the implications of technological development is that Digital learning material (DLM) is used to deliver a variety of diverse material with a variety of content such as written text, audio, audio visual, animation, and interactive practice questions. This activity is a training for teachers related to the use of DLM in elementary school learning to deal with the industrial revolution 4.0 to improve teacher competency and optimize learning activities. The method used is discussion, simulation and practice. The activity was followed by elementary school teachers in the city of Tasikmalaya at SDN 1 Gunungpereng. The results of the activity got a very good response and provided knowledge and skills for teachers using DLM in learning. With this activity the teacher is able to understand and master the use of DLM in learning in elementary schools.Keywords: DLM, industrial revolution 4.0